COMPARATIVE STUDY OF HIGHER EDUCATION ADMINISTRATION INDONESIA–USA - Khoiria, Lailatul; Aminullah (International Journal of Multidisciplinary Reseach, 2026)
This article examines the comparative characteristics of higher education administration in Indonesia and the United States from the perspective of public administration. Using a library research method with a descriptive-comparative approach, this study analyzes bureaucratic structures, systems of governance, administrative reforms, and their implications for public service delivery in higher education. Indonesia represents a centralized-decentralized hybrid model with strong ministerial control, while the United States reflects a decentralized and market-oriented governance system. The findings show that differences in bureaucratic traditions, political systems, and administrative reforms significantly influence institutional autonomy, accountability mechanisms, and service quality. The Indonesian system emphasizes national standardization and equity, whereas the U.S. system prioritizes institutional autonomy, competition, and innovation. This study contributes to comparative public administration literature by providing insights into how administrative structures shape higher education governance and public service outcomes.